Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.11628/ksppe.2023.26.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Growth and Leaf Color Quality of <italic>Mesembryanthemum cordifolium</italic> f. <italic>variegata</italic> as Affected by Shading Levels

Abstract: Background and objective: <i>Mesembryanthemum cordifolium</i> is a plant belonging to the Aizoaceae family and is native to South Africa and Namibia. As a CAM plant, <i>M. cordifolium</i> exhibits strong resistance to drought stress and can be utilized for the removal of soil salinity and heavy metals. Furthermore, it is an important medicinal crop with anti-inflammatory and antidepressant effects. However, despite its potential benefits, research on the optimal growth environment for &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…CIELAB L * , a parameter indicating color lightness in the CIELAB, was high under 3000 and 4100 K white LEDs, at 41.36 and 41.33, respectively. Previous studies on day and night temperatures (Lee et al, 2023), shading levels (Lee and Nam, 2023a;Nam et al, 2022), and light quality (Lee and Nam, 2023c) reported that L * also in- with the parameters of plant growth (Lee and Nam, 2023b;Lee et al, 2022d;2023); and this study also found that under 3000 and 4100 K white LEDs, L * and b * also tended to be inversely proportional to FW and DW. Accordingly, it is expected that b * , like L * , can also be used as a stress index in plants.…”
Section: Vegetative Indices and Leaf Color Analysissupporting
confidence: 71%
“…CIELAB L * , a parameter indicating color lightness in the CIELAB, was high under 3000 and 4100 K white LEDs, at 41.36 and 41.33, respectively. Previous studies on day and night temperatures (Lee et al, 2023), shading levels (Lee and Nam, 2023a;Nam et al, 2022), and light quality (Lee and Nam, 2023c) reported that L * also in- with the parameters of plant growth (Lee and Nam, 2023b;Lee et al, 2022d;2023); and this study also found that under 3000 and 4100 K white LEDs, L * and b * also tended to be inversely proportional to FW and DW. Accordingly, it is expected that b * , like L * , can also be used as a stress index in plants.…”
Section: Vegetative Indices and Leaf Color Analysissupporting
confidence: 71%